Facility Layout Planning for Pyrolyzer Production Using Automated Layouts Design Program (ALDEP) Method - Achmad Pratama Rifai; Arief Rahman Alfithra; Chanif Faruq Al'adiat; Wangi Pandan Sari (OPSI, 2023)
One important factor to consider in increasing productivity in a company is the design of the facility layout. PT Hari Mukti Teknik is keen producing pyrolysis machine to contribute to addressing waste issue in Indonesia. Currently, the facility layout at the company is not suitable to produce pyrolizers as it was set up to produce industrial scale washing machines. To improve production efficiency, PT Hari Mukti Teknik needs facility layout that can be optimized for pyrolizers. The purpose of this study is to provide a layout design proposal for the pyrolysis machine manufacturing process to obtain an effective and efficient process. Here, we used ALDEP method to produce layouts based on consideration of the level of relationship between departments. There were 4 alternatives for the manufacturing and production and two alternative layouts for employee and office area. The design for new layout was selected based on the closeness relationship between the departments. An overall facility layout plan that is required for the production of pyrolysis machines is a building area the total of 1045 m² covering manufacturing, production, employee, office and parking space areas.